ANALISIS RASIO PROFITABILITAS UNTUK MENGUKUR KINERJA KEUANGAN PADA PT UNILEVER INDONESIA TBK. TAHUN 2017 – 2021 - Titik Yiping Devina Damayanti; Retnosari (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2022)
Company performance is an analytical tool carried out by company management in order to determine the financial condition of a company and also to measure the level of success of an organization or company in generating profits. Performance appraisal is important to do so that management can see the development of the company, especially go public companies that have been listed on the IDX. The purpose of this study is to assess the company's performance using profitability ratio analysis from PT Unilever Indonesia Tbk. using the 2017-2021 period. This research is a research with descriptive analysis method using time series method. This study uses secondary data obtained from the annual financial statements of PT Unilever Indonesia Tbk. for the years 2017-2021. The profitability ratio analysis used in this study includes NPM, ROA and ROE. From the results of calculations and comparisons, it can be concluded that NPM and ROA fluctuated, while ROE also fluctuated but tended to increase. When compared with the average in the previous period, it can be concluded that the company is in a bad condition.